Determinants of Data Use for Decision Making in Health Facilities in Kitui County, Kenya (Quest Journal of Management and Social Sciences, 2021)
Background: Effective management of today’s health systems depends on the critical use of data for the policy-making, planning, monitoring of services, and making decisions. The use of data has been limited and faced with inadequacy hence vital health decisions often relying on political opportunism, donor demand, and infrequently repeated national studies which are insensitive to changes occurring over a shorter timescale.Objective: This study was designed to identify determinants of utilization of routine data for decision making by health care providers in health facilities in Kitui County in Kenya.Methods: The conceptual framework was constructed from the literature review. This was a descriptive cross-sectional study adopting quantitative and qualitative research paradigms. The district hospital was purposively selected. Multi-stage cluster sampling was used to sample the health facilities in sub-counties and simple random sampling to select the respondents from different cadres in health facilities. The 110 participants completed a self-administered questionnaire. Key informant interviews, focused group discussions, observation, and analysis of documents in health facilities were applied. Recordings were transcribed and key concepts identified. Questionnaire results were edited, coded, tabulated, and analyzed using the SPSS 18.Results: Respondents interviewed were different cadres of health care providers including doctors, clinical officers, nurses, and midwives from different levels of health facilities. Among the respondents, 70% were females, and 30% males.  The majority, 64% had a diploma level of education. Nurses/ midwives were the majority, making up 81% of the workforce. The overall extent of data utilization was 66% not using data and 34% use the routine generated data. The following actors influence utilization of routine data: frequency of meetings held (Χ2 =42.036, df=1, p=0.001), data storage and analyzing methods (Χ2 = 30.582, df=1, p=0.001), and continuous professional training (Χ2 = 49.782, df=1, p=0.0001). Organization of the district health system influenced routine data utilization through the frequency of support supervision (Χ2 =30.000, df=1, p=0.001), issues assessed during supervision (Χ2 =49.164, df=2, p=0.002) and feedback report from the supervisors (Χ2 =5.236, df=1, p=0.022).Conclusion: The study demonstrated limited utilization of routine data for decisions in health facilities and recommended the need for capacity building for data utilization through on job training and strengthening the curriculum in health training institutions in data-related areas. The ministry of health can standardize the parallel reporting levels and unify the reporting tools and finally ensure the districts have structured meetings, support supervision, and feedback to the health care providers.